2018
DOI: 10.1128/aac.00341-18
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Gastrointestinal Colonization and Acquisition of Carbapenem-Resistant Gram-Negative Bacteria among Patients in Intensive Care Units in Thailand

Abstract: This study was conducted to investigate the prevalence of and risk factors for colonization and acquisition of carbapenem-resistant (CR) Gram-negative bacteria (GNB) among patients admitted to intensive care units (ICUs) in two tertiary care hospitals in northern Thailand. Screening of rectal swab specimens for CR-GNB was performed on patients at ICU admission and discharge. The phenotypes and genotypes of all isolates were determined. Risk factors were analyzed by logistic regression analysis. The overall car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
38
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 37 publications
4
38
0
2
Order By: Relevance
“…In China, the overall annual CRE incidence is approximately 4 per 10,000 discharges, with the highest rates in some regions (0.15%) where CRE is highly endemic and causes a severe disease burden [22]. Active surveillance for CRE colonization as part of a multifactorial intervention is an effective strategy to decrease nosocomial CRE infection rate and CRErelated mortality [20,23,24]. CRE screening with stool is considered an effective method for surveillance of CRE colonization.…”
Section: Discussionmentioning
confidence: 99%
“…In China, the overall annual CRE incidence is approximately 4 per 10,000 discharges, with the highest rates in some regions (0.15%) where CRE is highly endemic and causes a severe disease burden [22]. Active surveillance for CRE colonization as part of a multifactorial intervention is an effective strategy to decrease nosocomial CRE infection rate and CRErelated mortality [20,23,24]. CRE screening with stool is considered an effective method for surveillance of CRE colonization.…”
Section: Discussionmentioning
confidence: 99%
“…In China, the overall annual CRE incidence is approximately 4 per 10,000 discharges, with the highest rates in some regions (0.15%) where CRE is highly endemic and causes a severe disease burden [23]. Active surveillance for CRE colonization as part of a multifactorial intervention is an effective strategy to decrease nosocomial CRE infection rate and CRE-related mortality [24][25][26]. CRE screening with stool is considered an effective method for surveillance of CRE colonization.…”
Section: Discussionmentioning
confidence: 99%
“…16 CR isolates of K. pneumoniae are known to be associated with high mortality and morbidity rates due to limited available therapeutic alternatives, indicating the importance of detection strategies. [14][15][16][17][18] Based on the results of the current study, 3 (4.3%) K. pneumoniae isolates were CRKP among which two of them were blaNDM positive. Moreover, a comprehensive meta-analysis conducted to estimate the prevalence of CRKP in different provinces of Iran indicated that 11% of the isolated K. pneumoniae were CR, ranging from 0.004 in Tehran to 58% in Isfahan provinces.…”
Section: Discussionmentioning
confidence: 99%
“…15 These contradictory results may be related to the low quality of personal hygiene, [14][15][16][17][18] variable sample sizes, the indiscriminate use of antibiotics, poor infection control policies, and the presence of some risk factors like previous hospitalization and long-term staying at ICU. [14][15][16][17][18] The results of the current study further revealed that 4.3% of isolates were MBL enzymes positive using imipenem-EDTA combined disk test. Among them, two isolates were blaNDM positive while the other investigated resistance genes were not detected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation